1996
DOI: 10.1029/96ja00460
|View full text |Cite
|
Sign up to set email alerts
|

Detection of localized, plasma‐depleted flux tubes or bubbles in the midtail plasma sheet

Abstract: Recent studies have shown that most Earthward transport hi the midtail, high‐beta plasma sheet takes place in the form of short‐lived, high‐speed plasma flow bursts. Bursty bulk flows are observed both when the plasma sheet is thin, such as during substorm expansion, and when it is thick, such as during substorm recovery. We present multi‐instrument observations from the ISEE1 and ISEE 2 spacecraft to argue that when the plasma sheet becomes thick and close to its equilibrium state, the plasma and magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
372
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 300 publications
(421 citation statements)
references
References 19 publications
48
372
1
Order By: Relevance
“…Intensifications of the electric fields correspond to local depletions of the plasma pressure. While a net increase in plasma pressure has often been observed in the inner plasma sheet [e.g., Miyashita et al, 2009;Xing et al, 2010], the local depletion of the plasma pressure that we observed is similar to the one observed in the midtail plasma sheet (∼20 R E ), where earthward flows enhance with entropy reduction [e.g., Sergeev et al, 1996].…”
Section: The Westward Expansion On 26 February 2008mentioning
confidence: 55%
“…Intensifications of the electric fields correspond to local depletions of the plasma pressure. While a net increase in plasma pressure has often been observed in the inner plasma sheet [e.g., Miyashita et al, 2009;Xing et al, 2010], the local depletion of the plasma pressure that we observed is similar to the one observed in the midtail plasma sheet (∼20 R E ), where earthward flows enhance with entropy reduction [e.g., Sergeev et al, 1996].…”
Section: The Westward Expansion On 26 February 2008mentioning
confidence: 55%
“…Azimuthal perturbations of the magnetic ®eld and velocity measurements associated with BBFs were also discussed by Baumjohann et al (1990), who suggested an association with the limited azimuthal extent of the¯ow region. Some evidence of a systematic relationship between the direction of the V y perturbation and the azimuthal location of the observing spacecraft, such that V y was directed away from the midnight sector, has recently been presented by Sergeev et al (1996) at a distance of 20 R E downtail, who interpreted BBFs in terms of plasma sheet bubbles (Chen and Wolf, 1993), probably caused by reconnection in the magnetotail. Indeed, the ground magnetometer features presented here are similar to those of Kauristie et al (1996), which were again interpreted in terms of plasma sheet bubbles.…”
Section: Relationship To Substorm Theoriesmentioning
confidence: 99%
“…[60] Comparing the ECR and BBF scale sizes, observational investigations have confirmed that BBFs are narrow and elongated structures, whose cross-tail scale size is of the order of 1 or a few R E [e.g., Sergeev et al, 1996a;Angelopoulos et al, 1997;Nakamura et al, 2004Nakamura et al, , 2005aWalsh et al, 2009]. Walsh et al [2009] estimated that the BBF size along the direction of the plasma flow is approximately ∼4R E .…”
Section: Ecr Scale Sizementioning
confidence: 99%
“…As shown by Birn et al [2004], flow vortices appear at the flanks of the bubble, twisting the magnetic field, and causing a downward (upward) field-aligned current at the dawnside (duskside) flank, and forming a local wedge like current system [e.g., Wolf, 1993, 1999;Sergeev et al, 1996a;Birn and Hesse, 1996;Birn et al, 1999Birn et al, , 2004Snekvik et al, 2007;Zhang et al, 2009]. A return plasma flow may occur at the flanks of the bubble, and the corresponding shear against the plasma flow in the bubble main channel may also be involved in the generation of the field-aligned currents [e.g., Chen and Wolf, 1999;Kauristie et al, 2000;Birn et al, 2004;Keiling et al, 2009;Ohtani et al, 2009;Walsh et al, 2009;Panov et al, 2010aPanov et al, , 2010bBirn et al, 2011;Ge et al, 2011;Pitkänen et al, 2011].…”
Section: Introductionmentioning
confidence: 99%